The African Church’s application of anointing oil: An expression of Christian spirituality or a display of fetish ancestral religion? - Biwul, Joel K. (HTS Teologiese Studies / Theological Studies, 2021)
The content of Christian spirituality that made waves since the inception of the early church soon took on different contours as the faith got adapted to different gentile contexts. The expression of this faith, along with its liturgical symbolism and sacramental observances, is still gaining momentum in African Christianity. The emerging practice of the use of ‘anointing oil’ in its religious expression is receiving more attention than the Christ of the Gospel. In this article, we argue that against its primitive intent, the use of the ‘anointing oil’ by the African Church is a mere display of fetish ancestral religion that expresses its unique African traditional religious root rather than a true expression of Christian spirituality. Our thesis is framed on the basis that the manner in which some African churches apply the purported ‘anointing oil’ is discriminatory vis-à-vis its ancient understanding and purpose. In our attempt to address this damaging practice to true Christian spirituality, also standing as a huge challenge for pastoral theology, we undertook a careful historical–theological analysis of the extant biblical data and its contextual interpretation vis-à-vis its distortion today. We concluded that what pastoral theologians have to deal with within the Christian community in Africa is offering the right biblical perspective against the distorted mode of the application of the contemporary purported ‘anointing oil’ that is falsely projecting the Christian faith and belief in a bad light. Contribution: The application of the anointing oil in contemporary Christian religion in Africa is, to say the least, not an inherent textually prescribed requisite criterion for Christian spirituality, but merely an outburst of fetish ancestral religious worldview that stands contra the hermeneutics of the biblical text and its ancient tradition. That no Old Testament prophet, not even Jesus nor Paul, mentioned the subject, makes its contemporary application textually and theologically suspect, and therefore, heretically infectious for the spiritual health of the community of faith. These insights sit quite well with the textual hermeneutics within the mainline transdisciplinary religious and multidisplinary theological perspective of this journal.
free